Alzheimer's and the Indian Appetite - Brijnath, Bianca (2011)
Activities such as cooking, feeding, and eating speak to the pleasures and difficulties of caring for a person with dementia. In this article, I draw on ethnographic data from Delhi to examine the links between three types of food and caregiving in relation to sweetness and pleasure, drug foods and containment, and the feeding tube and sustaining life. I will illustrate that food offers ways to retain identity, build relations, improve function, and show love. In so doing, I contribute to our understanding of how care is conceived cross-culturally and offer potential insight into how interventions using food can enhance personal relationships in home and institutional settings.